2012
DOI: 10.3758/s13423-011-0199-1
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual distinctiveness produces long-lasting priming of pop-out

Abstract: Maljkovic and Nakayama (1994) demonstrated memory influences in singleton search from one trial to the next, an effect they termed priming of pop-out (PoP). This effect was described as resulting from the persistence of an implicit memory trace, the influence of which could be observed for around five to eight subsequent trials. The seemingly short-lived nature of this priming effect has been attributed to decay of the underlying memory representation that occurs when attention is directed to intervening searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…Recent work from our lab however, has shown that the number of trials over which PoP can be measured is strongly affected by contextual reinstatement that is both perceptual (Thomson & Milliken, 2012) and nonperceptual (Thomson & Milliken, in press) in nature, suggesting that retrieval interference may at least partially dictate the magnitude of PoP effects. In addition, recent theoretical accounts of PoP have been forwarded that acknowledge a role for both feed-forward mechanisms, as well as episodic retrieval contributions to the PoP effect (Lamy, Yashar, & Ruderman, 2010;Yashar & Lamy, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…Recent work from our lab however, has shown that the number of trials over which PoP can be measured is strongly affected by contextual reinstatement that is both perceptual (Thomson & Milliken, 2012) and nonperceptual (Thomson & Milliken, in press) in nature, suggesting that retrieval interference may at least partially dictate the magnitude of PoP effects. In addition, recent theoretical accounts of PoP have been forwarded that acknowledge a role for both feed-forward mechanisms, as well as episodic retrieval contributions to the PoP effect (Lamy, Yashar, & Ruderman, 2010;Yashar & Lamy, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…The results of the present work are important in several ways: (1) while there are now numerous demonstrations that attention capture effects are modulable by explicit, top-down knowledge and strategy, only one other study (to our knowledge) has demonstrated that such effects are sensitive to implicit context-specific knowledge (Cosman and Vecera, 2012); (2) Behavioral effects in several other performance domains have been shown to be modulated by the match or mis-match in task irrelevant contextual information between prior experience and current perception (i.e., proportion congruency effects in the Stroop task—Crump et al, 2006; negative priming effects—Neill, 1997; conflict adaptation effects—Spapé and Hommel, 2008; long-lasting inhibition of return—Wilson et al, 2006; and long-lasting priming effects in singleton search—Thomson and Milliken, 2012, 2013a,b). The present work however, represents the first evidence that properties of the task-relevant stimuli themselves can bias search behavior in the context of the attention capture paradigm; and (3) While most prior studies showing that prior experience can bias the capture of attention by an irrelevant singleton can be explained via automatic, trial-to-trial influences (i.e., the operation of “short-term” priming), the ISPC effect observed here demonstrates that trial history beyond the most recent experience can affect the capture of attention by the most salient item in the search display.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have argued that this effect may owe, at least in part, to the automatic retrieval of similar prior episodes (Hillstrom, 2000; Huang et al, 2004; Thomson and Milliken, 2011). For example, it has been shown that the speed with which singleton search unfolds depends on whether the features of the target match those in the most recent contextually similar trial (Thomson and Milliken, 2012, 2013a). Additionally, when many prior experiences are contextually similar to the current one, priming effects are dependent on the number of intervening experiences that occurred between the current and “influencing” trial, which has been interpreted by some as evidence for a form of retrieval interference (Thomson and Milliken, 2013b; Experiment 3).…”
Section: Introductionmentioning
confidence: 99%
“…Such an interval should be long enough for successful encoding of even the categorical WM representation. The visual cue benefit could then be still due to visual priming, which has been suggested to last at least tens of seconds (Maljkovic and Nakayama, 2000; Thomson and Milliken, 2012). Note that in our Experiment 1, the benefits of the visually presented postcue were over after 400 to 1000 ms, but this was when comparing it against a visually initiated WM.…”
Section: Discussionmentioning
confidence: 99%